Adaptive backstepping tracking control for an over-actuated DP marine vessel with inertia uncertainties - Witkowska, Anna; Śmierzchalski, Roman (Zielona Góra: Uniwersytet Zielonogórski)
Designing a tracking control system for an over-actuated dynamic positioning marine vessel in the case of insufficient information on environmental disturbances, hydrodynamic damping, Coriolis forces and vessel inertia characteristics is considered. The designed adaptive MIMO backstepping control law with control allocation is based on Lyapunov control theory for cascaded systems to guarantee stabilization of the marine vessel position and heading.
Keywords: over-actuated control; adaptive control; Lyapunov function; control allocation; MIMO systems